1984
DOI: 10.1093/infdis/149.3.378
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Monomeric Peptidoglycan Fragments from Neisseria gonorrhoeae to Damage Human Fallopian-Tube Mucosa

Abstract: Purified disaccharide peptide monomers obtained from Neisseria gonorrhoeae by enzymatic digestion of gonococcal peptidoglycan damaged the mucosa of human fallopian tubes in organ culture. Two peptidoglycan fragments were tested: a nonreducing, anhydromuramyl-containing monomer (the principal fragment shed by growing gonococci) and the analogous reducing, muramidase-derived monomer. The damage produced by either of these peptidoglycan monomers resulted in sloughing of ciliated cells from the mucosa and resemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
152
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(155 citation statements)
references
References 34 publications
2
152
1
Order By: Relevance
“…Although neither of these factors appears to contribute to the effect of Ng on HIV-1, it seems likely that they work in concert to make the mucosal tissues receptive to infection by and/or the persistence of the bacteria. Supporting this model, released peptidoglycan fragments are selectively toxic to mucosal ciliary cells so as to stop mucus flow and provide the bacteria access to the subepithelial space (48). Future efforts must consider the cumulative effect of these factors on the mucosal epithelia and their respective roles during Ng infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although neither of these factors appears to contribute to the effect of Ng on HIV-1, it seems likely that they work in concert to make the mucosal tissues receptive to infection by and/or the persistence of the bacteria. Supporting this model, released peptidoglycan fragments are selectively toxic to mucosal ciliary cells so as to stop mucus flow and provide the bacteria access to the subepithelial space (48). Future efforts must consider the cumulative effect of these factors on the mucosal epithelia and their respective roles during Ng infection.…”
Section: Discussionmentioning
confidence: 99%
“…The degree to which PG material is sloughed off by bacteria can greatly affect the host response to the infection. For instance, release of PG from Bordetella pertussis (153), Neisseria gonorrhoeae (274), Helicobacter pylori (423), and Vibrio fischeri (223) acts to stimulate inflammatory processes by binding specific pathogen recognition molecules.…”
Section: Do Mycobacteria Recycle Cell Wall Material?mentioning
confidence: 99%
“…The major fragments released are the 1,6-anhydrodisaccharide tripeptide monomer and the 1,6-anhydrodisaccharide tetrapeptide monomer (16). These PG fragments have potent biological effects, including killing ciliated fallopian tube cells (13), inducing inflammatory cytokine production (4), and causing arthritis (5). Previous studies in our laboratory found that mutations affecting lytic transglycosylases LtgA and LtgB lower PG monomer production but do not alter cell division (2; K. A.…”
mentioning
confidence: 99%